2008
DOI: 10.1007/s00300-008-0560-7
|View full text |Cite
|
Sign up to set email alerts
|

Benthic isopods (Crustacea, Malacostraca) from the Ross Sea, Antarctica: species checklist and their zoogeography in the Southern Ocean

Abstract: In this study isopod species of the Ross Sea were investigated. Literature until May 2008 was checked to provide an overview of all known and described species in the Ross Sea. This species checklist was then enlarged through material of the 19th Italica expedition in 2004. During this expedition for the first time a small mesh net (500 mu m) was used. Nine thousand four hundred and eighty one isopod specimens were collected during this expedition. Through this material the number of isopod species in the Ross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Moreover, many of the species recorded in our study have been shown to occur over wider depth ranges at other Antarctic sites (e.g. Hodgson 1910;Castello 2004;Choudhury and Brandt 2009), although bathymetric distribution of a species may differ between semi-closed basins such as the Admiralty Bay and open shelf sites. On the other hand, polychaetes and amphipods showed a clear depth zonation in the Admiralty Bay (Siciński 2004;Siciński 2010b, 2012; Ja_ zd_ zewska and Siciński 2017).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, many of the species recorded in our study have been shown to occur over wider depth ranges at other Antarctic sites (e.g. Hodgson 1910;Castello 2004;Choudhury and Brandt 2009), although bathymetric distribution of a species may differ between semi-closed basins such as the Admiralty Bay and open shelf sites. On the other hand, polychaetes and amphipods showed a clear depth zonation in the Admiralty Bay (Siciński 2004;Siciński 2010b, 2012; Ja_ zd_ zewska and Siciński 2017).…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, no studies have addressed exclusively distribution patterns of the isopod fauna. The areas studied most thoroughly in terms of the Southern Ocean Isopoda species richness are large basins, including the Ross Sea (Choudhury and Brandt 2009), the Weddell Sea (Brandt 1992), the Bellingshausen Sea (Brandt 1999) and the region of the South Shetland Islands (Castello 2004). Some recent studies tackled also the deep-sea isopod fauna from different parts of the Southern Ocean (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies of the Antarctic isopod fauna were dedicated to taxon− omy, and to large scale patterns of species richness and zoogeography (e.g. Brandt 1990Brandt , 1992Teodorczyk and Wagele 1994;Castello 2004;Brandt et al 2005;Kai− ser et al 2007Kai− ser et al , 2009Choudhury and Brandt 2009;Kaiser 2014, and references therein). There are few studies analyzing diversity and patterns of distribution at smaller scales, especially at the microhabitat level.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are ecologically important in terms of biomass ( Brey and Gutt 1991 ; Barnes and Brockington 2003 ), their role in biogeochemical cycles (C and N) ( Danovaro et al 1999 ; Moodley et al 2002 ; Nomaki et al 2005 ; Woulds et al 2007 ; Gooday et al 2008 ; Lebrato et al 2010 ; Piña-Ochoa et al 2010 ), and their trophic role in benthic ecosystems ( De Ridder and Jangoux 1982 ; De Ridder and Lawrence 1982 ; Gooday et al 1992 ; Danovaro et al 1999 ; Dauby et al 2001 ; Suhr et al 2003 ; De Broyer et al 2004 ; Nomaki et al 2008 ). They are also characterized by different biogeographic and diversity patterns, modes of speciation, and reproductive and dispersal mechanisms ( Watling and Thurston 1989 ; Brandt 1999 ; De Broyer and Rauschert 1999 ; Raupach and Wägele 2006 ; Brandt et al 2007 ; Murray 2007 ; Malyutina and Brandt 2007 ; Pawlowski et al 2008 ; Choudhury and Brandt 2009 ; Lecroq et al 2009 ). These five taxa are key contributors to the diversity and functioning of SO benthic ecosystems, but they are of course not the only benthic components playing an important role.…”
Section: Introductionmentioning
confidence: 99%